Susceptibility of Demotispa neivai (Coleoptera: Chrysomelidae) to Beauveria bassiana and Metarhizium anisopliae entomopathogenic fungal isolates. Issue 1 (14th September 2021) - Martínez, Luis Carlos; Plata‐Rueda, Angelica; Ramírez, Augusto; Serrão, José Eduardo
Abstract: BACKGROUND: The potential of Beauveria bassiana and Metarhizium anisopliae isolates obtained from naturally infected oil palm pests was evaluated to control Demotispa neivai as an alternative for organophosphate insecticide use in oil palm crops in Latin America. Two B. bassiana (Bb‐0018 and Bb‐0025) and two M. anisopliae (Ma‐0002 and Ma‐0003) isolates were tested against D. neivai adults for hydrophobicity, virulence, survival, adhesion to host cuticle, and mortality in semi‐field conditions. RESULTS: Concentration–mortality bioassays demonstrate that isolates had lethal effect on D. neivai adults with Bb‐0025 [median lethal concentration (LC50 ) = 3.45 × 10 7 conidia mL −1 ] and Bb‐0018 (LC50  = 3.75 × 10 7 conidia mL −1 ) being the most effective followed by Ma‐0003 (LC50  = 3.38 × 10 8 conidia mL −1 ) and Ma‐0002 (5.33 × 10 8 conidia mL −1 ). Adult survival was 99% without exposure to fungal isolates, decreasing to 21.65% in insects exposed to Ma‐0002, 19.41% with Ma‐0003, 20.13% with Bb‐0018, and 0.17% with Bb‐0025. Mortality of D. neivai adults caused by the entomopathogenic fungal isolates was similar in both laboratory and semi‐field conditions. Also, vegetative growth of the entomopathogenic fungal isolates was found in infected D. neivai adults in the field. CONCLUSION: Our data suggest that the tested entomopathogenic fungal isolates are effective against D. neivai with potential to be used as biological control agents contributing to the decrease of the use of chemical insecticides to control this oil palm pest. © 2021 Society of Chemical Industry. Abstract : Demotispa neivai is a chrysomelid pest of oil palm due to the damage caused to fruits. The use of native entomopathogenic fungi was explored as an alternative to organophosphate insecticides used to control this insect being a more sustainable management strategy.